Contrato e confiança: perspectivas para a construção de uma base pública de justificação para o direito contratual brasileiro - Henry Gabriel Colombi Barbosa Ferreira (2021)
This dissertation aims to offer an alternative theory to explain and justify theoretically Brazilian contract law. It starts by reviewing the literature about the evolutionary timeline of contract law theory, from the voluntaristic until the welfarist paradigm. It concludes that, despite the social and political evolution, the theoretical conceptions of contract law were not refunded by Welfare State theory of contract law. A claim is made that voluntaristic categories still prevail in Brazilian contract theory, which is only tempered by social views. Given de implausibility of the so-called “mitigated voluntaristic model”, an alternative proposal is offered and tested in its fitness as a public basis of justification of contract law: the reliance theory. First, the moral plausibility of this conception is proven. Then, the compatibility of the idea is contrasted with Brazilian positive contract law. The hypothesis is proven right, concluding that reliance theory can provide an explanatory and justificatory model to Brazilian contract law which is, in general, better than “mitigated voluntaristic model”, still mainstream in Brazilian doctrine.